2021
DOI: 10.3390/ijms23010259
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Current Landscape of SARS-CoV-2 Main Protease Inhibitors: Have We Hit the Bullseye Yet?

Abstract: In this review, we collected 1765 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) M-pro inhibitors from the bibliography and other sources, such as the COVID Moonshot project and the ChEMBL database. This set of inhibitors includes only those compounds whose inhibitory capacity, mainly expressed as the half-maximal inhibitory concentration (IC50) value, against M-pro from SARS-CoV-2 has been determined. Several covalent warheads are used to treat covalent and non-covalent inhibitors separately. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 108 publications
1
43
0
Order By: Relevance
“…To date, thousands of candidate SARS-CoV-2 Mpro inhibitor compounds have been screened so far in order to identify potent drug candidates [ 64 ], but many of them were shown to have no or only limited clinical potential since high concentration was usually required to achieve significant inhibition. Actually, most of the investigational 3CLpro inhibitors are of similar peptidomimetic scaffolds [ 65 ].…”
Section: Proteases Inhibitors and Mutationsmentioning
confidence: 99%
“…To date, thousands of candidate SARS-CoV-2 Mpro inhibitor compounds have been screened so far in order to identify potent drug candidates [ 64 ], but many of them were shown to have no or only limited clinical potential since high concentration was usually required to achieve significant inhibition. Actually, most of the investigational 3CLpro inhibitors are of similar peptidomimetic scaffolds [ 65 ].…”
Section: Proteases Inhibitors and Mutationsmentioning
confidence: 99%
“…[55,56] Several different types of inhibitors have been investigated including peptidomimetic covalent inhibitors, small molecule covalent inhibitors, and noncovalent inhibitors. [9,57] Historically, covalent inhibitors were thought to be generally cytotoxic due to off target effects; however, recent developments have shown that this is not always the case. Development of covalent cysteine proteases has shown significant potential for SARS-CoV-2 drug development.…”
Section: Sars-cov-2 3clpro Inhibitorsmentioning
confidence: 99%
“…Paxlovid, an oral SARS-CoV-2 M pro inhibitor, was recently approved to treat mild-to-moderate COVID-19 [41]. Many review articles show the effort put in to identify the most effective covalent and non-covalent inhibitors of the SARS-CoV-2 M pro [3,42,43]. All these studies show that M pro is one of the most promising viral targets for SARS-CoV-2 antiviral drug development.…”
Section: Introductionmentioning
confidence: 99%